Comparative Analysis of Plastic-Sand and Plastic-Clay Bricks: ‎Mechanical Properties, Environmental Impact, and Economic Viability (Journal of University of Babylon for Engineering Sciences, 2025)
The growing problem of plastic waste piling up around the world, along with the large environmental impact of traditional building materials, means that new ways of building that are good for the environment are needed.  This thorough study offers an in-depth comparative analysis of environmentally friendly bricks made from recycled plastic waste, employing two different filler materials: sand and clay.  The study methodically analyzes two production methods: a compression-heating technique for plastic-sand bricks and a firing process for plastic-clay bricks.  Brick samples were made with different plastic-to-filler ratios (10:90, 20:80, and 30:70 by weight) to test how well they worked in terms of compressive strength, fire resistance, water absorption, thermal insulation, durability, production costs, and environmental impact.  The results consistently show that plastic-sand bricks made by compression-heating are much better than plastic-clay bricks on most performance measures.  Plastic-sand bricks had a compressive strength of 23.7 MPa, very little water absorption (2.5%), and better thermal insulation properties (0.48 W/m·K) when the ratio was 30:70.  Plastic-clay bricks were more fire-resistant because they had a ceramic matrix, but they cost about 15% more to make because firing them takes a lot of energy.  The in-depth study finds that plastic-sand bricks are a better option for sustainable construction because they offer the best combination of mechanical strength, durability, cost-effectiveness, and environmental benefits. They are best for light structural and non-load-bearing uses.